KECUKUPAN KONSUMSI SAYUR DAN BUAH PADA SISWA SMA NEGERI 1 KUANTAN HILIR - Adhia Endrika; Erwin Christianto; Elda Nazriati (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTA problem related eating behaviour is low consumption of fruit and vegetable. The number of sufficiency of fruit and vegetable consumption that recommended by WHO 2003 is 500 gr each day or equal to 3-5 portion. Riskesdas 2007 had found 93,7% of 10-24 years old Indonesian teenagers that had low fruit and vegetable consumption. The aim of this research was to describe fruit and vegetable consumption in SMAN 1 Kuantan Hilir students. This was a cross-sectional descriptive study. This study showed most subjects had sufficient fruit and vegetable consumption, good intake of vitamin A, good knowledge of fruit and vegetable intake, and good attitude of fruit and vegetable intake.Keywords: WHO, teenager, fruit and vegetable, knowledge, attitude, vitamin A